AB0478 Systematic safety review of five biologic antirheumatic drugs. (23rd January 2014) - Stuart, M.E.; Shrite, S.A.; Gandra, S.R.
Abstract : Background: Decision-making regarding therapeutic intervention depends on various factors, including knowledge of the risk-benefit profile of each agent. The relative safety of antirheumatic biologic agents is difficult to assess because of the paucity of direct comparative data, relative rarity of adverse events (AEs), and study design and patient population heterogeneity. Objectives: Review clinical trial and observational study evidence regarding comparative safety of 5 biologics used in the treatment of rheumatoid arthritis (RA), psoriasis, and psoriatic arthritis: adalimumab (ADA), certolizumab pegol (CZP), etanercept (ETN), golimumab (GLM), and infliximab (IFX). Methods: Search strategy for this systematic safety review utilized: PubMed, Cochrane Databases, Agency for Healthcare Research and Quality (AHRQ), FDA databases and selected studies from bibliographies of retrieved studies. Search terms: DMARD, tumor necrosis factor, the 5 biologics names, FDA-approved conditions, and associated AE types. Studies were evaluated for inclusion based on validity and clinical relevancy. Findings were graded for evidence strength using a modified AHRQ approach: high, moderate, borderline or inconclusive. Results: In total, 73 publications were included. Numeric differences were observed in the safety profiles of the 5 biologics. Borderline evidence (Table) indicated RA patients treated with ETN compared to those treated with ADA and IFX may have lower risk for serious infections and withdrawal due to AEs. Inconclusive evidence suggested RA patients treated with ADA, ETN, GLM, and IFX may have lower risk for serious infections (SIs) than those receiving CZP. Across studied populations, borderline evidence indicated lower risk with ETN for tuberculosis (TB) than with ADA or IFX, and inconclusive evidence indicated that ETN had a lower risk for opportunistic infections (OIs) and lymphoma than ADA or IFX. Conclusions: Although the evidence was rated as borderline or inconclusive using a modified AHRQ approach, our systematic review found patterns suggesting differences among ETN, ADA, and IFX in some safety outcomes. These findings add to the existing body of literature to inform managed care formulary decisions. This study was sponsored by Immunex, a wholly owned subsidiary of Amgen Inc. and by Wyeth, which was acquired by Pfizer Inc. in October 2009. Disclosure of Interest: M. Stuart Consultant for: Amgen Inc, S. Shrite Consultant for: Amgen Inc, S. Gandra Employee of: Amgen Inc